Experimental study on adsorption of a new surfactant onto carbonate reservoir samples—application to EOR. (18th March 2013) - Zendehboudi, Sohrab; Ahmadi, Mohammad Ali; Rajabzadeh, Amin Reza; Mahinpey, Nader; Chatzis, Ioannis
Abstract Surfactant flooding aims at lowering the interfacial tensions between the oil and water phases to improve the displacement efficiency during oil recovery. However, surfactant losses due to adsorption on the reservoir rock impairs performance of the chemical flooding, consequently renders the process impractical economically. This article presents adsorption equilibrium and kinetics of Zizyphus Spina Christi (ZSC), a new non‐ionic surfactant, onto carbonate rocks. The adsorption tests were conducted at a temperature range of 28–75°C. A conductivity method was employed in this study to measure CMC parameter and surfactant concentration in the aqueous solutions. The equilibrium conditions for the crushed rock samples were obtained after about 2 days. According to the experimental results, the equilibrium data were well‐fitted by the Freundlich isotherm for carbonate samples. Furthermore, the adsorption process is exothermic and obeys the second‐order kinetic model. Such a systematic investigation is very helpful to select a proper surfactant for EOR application and reservoir stimulation in the petroleum industry.